Society, environment and frontier in the Amazon: some historical and political topics - Santos, Nelvio Paulo Dutra (Textos e Debates, 2016)
This work is the result of thematic discussions on topics covered during the First International Seminar on Society and Frontiers, sponsored by PPGSOF/UFRR, on December 2012 in Boa Vista. Here we try to establish some relationships between the categories society, environment and frontier in the Amazon, especially from the perspective of political and administrative developments, from colonial times to recent times. The Amazon frontier is characterized here as nothing more than a historical supplier of natural resources as well as more than a space delimited by the National State. Its traditional inhabitants are seen as builders of their own space, and are also incorporated into projects of the National State in order to meet existing demands elsewhere, either at the beginning of the conquest or at present. In short, it is how the economics and politics overcome peoples and environment and shaped life in the area known today as the Brazilian Amazon.